Fair Trade Certification and Its Influence on International Markets - Porhomovici, Kateřina (2025)
This bachelor's thesis introduces the Fairtrade International certification system and examines the causes behind the unequal distribution of trade benefits, as well as how Fairtrade seeks to address these issues. It explores both the advantages of Fairtrade certification and its common criticisms. Drawing on case studies from three key regions (Latin America, Africa, and Asia), the thesis analyzes data to assess the actual impact of Fairtrade certification. In conclusion, it offers recommendations for improving the certification system to enhance its effectiveness.